SURFACE TEMPERATURE CHARACTERISTICS OF FLY ASH BOTTOM ASH BRICK AGAINST SUN LIGHTS - Vira Ansari; Eddy Prianto; Agung Dwiyanto (Ide dan Dialog Desain Indonesia (Idealog), 2022)
Fly Ash and Bottom Ash are by-products produced from the coal combustion process in Steam Power Plants (PLTU). In accordance with PP101 of 2014, Fly Ash and Bottom Ash (FABA) are included in the B3 Waste category that requires special treatment in accordance with applicable regulations. At this time, the Republic of Indonesia Government Regulation No. 22 of 2021 concerning the Implementation of Environmental Protection and Management, where FABA is included in Registered Non-B3 Waste. With these changes, it is hoped that FABA can be used extensively (massively) and continuously. Based on these developments, it is necessary to test the FABA material as a building wall to determine the temperature obtained when exposed to hot sunlight so that in the future the FABA material can be used as a reference as a material for the manufacture of building materials. This research method uses qualitative research methods, where this study aims to analyze the walls of the building using the model as the object of research, on the reduction of the sun with the influence of sunlight, humidity, and air temperature. The results of this study are to determine the wall temperature of FABA which includes: high peak temperature and lowest temperature. The findings obtained are that the orientation of sunlight af ects the temperature or the resulting temperature in the FABA wall model and for further research it is better to use a cover/roof in order to get the ideal temperature like the original building wall covered with a roof. Keywords : Bottom ash, Fly ash, Weather Conditions, FABA Wall